Enzymatic degradation of organophosphorus insecticides decreases toxicity in planarians and enhances survival. Issue 1 (December 2017) - Poirier, Laetitia; Brun, Lucile; Jacquet, Pauline; Lepolard, Catherine; Armstrong, Nicholas; Torre, Cédric; Daudé, David; Ghigo, Eric; Chabrière, Eric
Abstract Organophosphorus insecticides (OPs) are toxic compounds used for agricultural purposes and responsible for severe types of contamination worldwide. OPs may also induce chronic deleterious effects and developmental disruption. Finding remediation strategies is a major concern to diminish their impact on environment and human health. Enzymes have emerged as a promising eco-friendly route for decontaminating OPs. The enzymeSso Pox from the archaeaSulfolobus solfataricus has been particularly studied, considering both its tremendous stability and phosphotriesterase activity. However, the toxicity of the degradation products generated through enzyme hydrolysis has been poorly investigated. To address both neurotoxicity and developmental perturbation, freshwater planarians from Platyhelminthes were considered to evaluate the impact of OP and degradation product exposure. Planarians have a large proportion of stem cells that give them an unconventional capacity for regeneration. OPs were found to be highly toxic to planarians and enzyme decontamination drastically enhanced survival rate. Although not completely innocuous, the degradation products were found to be less toxic than insecticides and reduced poisoning effects by increasing NOEC values by up to eight-fold.Sso Pox also limited detrimental consequences on planarian mobility and enabled them to recover a non-exposed type regeneration process suggesting that enzymatic decontamination is a promising alternative to bioremediation.